Baseline PET-CT evaluation of Bone Marrow-Liver-Spleen Type of Diffuse Large B-Cell Lymphoma: A Rare Aggressive Extranodal Lymphoma - Hossain, Sadia; Rahman, Farhana; Afrin, Rawnak; Afrin, Afroza; Biswas, Shanker; Biswas, Tanima; Sultana, Tania; Islam, Sabrina; Sharmin, Shaila; Begum, Rubina; et al. (Bangladesh Journal of Nuclear Medicine, 2024)
Bone marrow-liver-spleen (BLS) type lymphoma is a rare subgroup of diffuse large B-cell lymphoma, characterized by bone marrow involvement without lymph nodes. Symptoms include fever, anemia, and hemophagocytic lymphohistiocytosis. Early diagnosis and treatment are crucial for proper management and prevention. We report a case of a 59-year-old male with diffuse large B-cell lymphoma (DLBCL) involving bone marrow. He was diagnosed with a bone marrow-liver-spleen (BLS) subtype of lymphoma with the help of F-18 FDG PET-CT. BLS is an unusual subgroup of extra-nodal DLBCL. Very few cases have been reported to date. The disease showed unique clinico-pathological features of involvement of bone marrow with or without liver and/or spleen, but no lymph node or other extra-nodal sites are involved, hence the name BLS. Bangladesh J. Nuclear Med. 27(1): 112-116, 2024